2022
DOI: 10.2147/jir.s356841
|View full text |Cite
|
Sign up to set email alerts
|

m6A Regulator-Mediated Methylation Modification Patterns and Characterisation of Tumour Microenvironment Infiltration in Non-Small Cell Lung Cancer

Abstract: Purpose The role of RNA N6-methyladenosine (m 6 A) modification in the progression of multiple tumours and the tumour microenvironment (TME) has been progressively demonstrated and promises a new direction for tumour therapy. However, there have been no reports on systematic analyses of RNA m 6 A modification in TME in non-small cell lung cancer (NSCLC). Patients and Methods In this study, we used unsupervised cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Analysis of correlation between the levels of CD69 and SBK1, and infiltrating immune cells and IPS. predict response to CTLA-4 and PD-1 blockade and has been used in an increasing number of studies (52)(53)(54). Here, we show that in various tumors, IPS correlates positively and negatively with CD69 and SBK1 expression levels, respectively.…”
mentioning
confidence: 59%
“…Analysis of correlation between the levels of CD69 and SBK1, and infiltrating immune cells and IPS. predict response to CTLA-4 and PD-1 blockade and has been used in an increasing number of studies (52)(53)(54). Here, we show that in various tumors, IPS correlates positively and negatively with CD69 and SBK1 expression levels, respectively.…”
mentioning
confidence: 59%
“…The complexity of immune cell infiltration in the tumor microenvironment is one of the leading causes of LUAD treatment efficacy. According to bioinformatics analysis studies, m6A regulators are correlated with tumor prognosis and the immune microenvironment (Fan et al, 2022;Xiong et al, 2022). Two m5C modification patterns had different immune cell-infiltrating subtypes, illustrating that m5C might regulate the LUAD immune microenvironment (Chen et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no reports yet on the regulatory mechanisms of WTAP in tumor immunity, one of the tumor hallmarks. Studies have revealed that the tumor microenvironment of patients can be classified into ‘immunoinflammatory’, ‘immune evasion’, and ‘immunodesert’ based on m 6 A-regulated gene expression by unsupervised clustering analysis [ 159 , 160 , 161 ]. Different immune-system phenotypes have different immunotherapeutic effects, and choosing the appropriate treatment plan according to different phenotypes is in line with the modern concept of precision therapy.…”
Section: Discussionmentioning
confidence: 99%